Isolation and characterization of gelatin-binding proteins from goat seminal plasma - Lazure Claude; Manjunath Puttaswamy; Villemure Michèle (BMC, 2003)
Abstract A family of proteins designated BSP-A1, BSP-A2, BSP-A3 and BSP-30 kDa (collectively called BSP proteins for Bovine Seminal Plasma proteins) constitute the major protein fraction in the bull seminal plasma. These proteins interact with choline phospholipids on the sperm surface and play a role in the membrane stabilization (decapacitation) and destabilization (capacitation) process. Homologous proteins have been isolated from boar and stallion seminal plasma. In the current study we report the isolation and preliminary characterization of homologous proteins from goat seminal plasma. Frozen semen (-80°C) was thawed and centrifuged to remove sperm. The proteins in the supernatant were precipitated by the addition of cold ethanol. The precipitates were dissolved in ammonium bicarbonate and lyophilised. The lyophilised proteins were dissolved in phosphate buffer and loaded onto a gelatin-agarose column, which was previously equilibrated with the same buffer. The column was successively washed with phosphate buffer, with phosphate buffer saline and with 0.5 M urea in phosphate buffer saline to remove unadsorbed proteins, and the adsorbed proteins were eluted with 5 M urea in phosphate buffer saline. Analysis of pooled, dialysed and lyophilised gelatin-agarose adsorbed protein fraction by SDS-PAGE indicated the presence of four protein bands that were designated GSP-14 kDa, GSP-15 kDa, GSP-20 kDa and GSP-22 kDa (GSP, Goat Seminal Plasma proteins). Heparin-affinity chromatography was then used for the separation of GSP-20 and -22 kDa from GSP-14 and -15 kDa. Finally, HPLC separation permitted further isolation of each one from the other. Amino acid sequence analysis of these proteins indicated that they are homologous to BSP proteins. In addition, these BSP homologs bind to hen's egg-yolk low-density lipoproteins. These results together with our previous data indicate that BSP family proteins are ubiquitous in mammalian seminal plasma, exist in several forms in each species and possibly play a common biological role.